Scrotal Calcinosis: A Case Report and Review of Pathogenesis and Surgical Management - Usman M. Tela; M. Bashir Ibrahim (Case Reports in Urology)
Idiopathic scrotal calcinosis is an uncommon benign disorder of the scrotal skin which is characterized by multiple calcified intradermal nodules. We report a 33-year old with asymptomatic multiple calcified scrotal skin nodules. He had wide excision of the lesions and direct closure of the scrotum. We review the pathogenesis and surgical treatment options for this rare disease of the scrotum.